Factors Influencing the Adoption of Antibody-Drug Conjugates in Oncology: A Statistical Study - Sabrina Rahman, Sabrina Rahman; Rashid, Sana; Mehwish; Hussain, Ubaida; Ahmad Khan, Zafar; Patowary, Asma Ul Hosna; Munir, Atif (Indus Journal of Bioscience Research, 2024)
Hepatitis Antibody-Drug Conjugates (ADCs) represent a promising targeted therapy combining monoclonal antibodies with chemotherapy agents, offering enhanced therapeutic efficacy and reduced toxicity to normal cells, particularly in oncology. Despite this potential, widespread adoption remains constrained by key challenges. This study investigates the utilization of ADCs in oncology, focusing on clinical outcomes, safety, costs, regulatory hurdles, and healthcare professionals’ awareness. A survey of 200 healthcare professionals, including oncologists, pharmacists, and administrators, was conducted to assess expectations and experiences with ADCs across clinical value, cost, and compliance dimensions. Data analysis was performed using SPSS, employing descriptive statistics, ANOVA, Chi-Square tests, and logistic regression. Results revealed clinical effectiveness and safety as primary factors influencing ADC adoption. However, significant barriers included costs (47%) and regulatory issues (52%), limiting broader application. A Chi-Square analysis indicated a significant correlation between the frequency of ADC recommendation and healthcare professionals’ exposure to ADC-related concepts, underscoring the importance of familiarity in promoting ADC use. ANOVA demonstrated cost concerns were more pronounced in private hospitals compared to public institutions. Logistic regression highlighted clinical effectiveness and technological advancements as the strongest predictors of ADC adoption. The findings suggest prioritizing cost-reduction strategies, streamlining regulatory processes, and enhancing awareness through education campaigns to increase ADC utilization. Future strategies should emphasize competitive pricing, improved regulatory clarity, and expedited approval processes to facilitate broader access to these life-saving therapies in oncology.